A Comparison of Public and Police Perceptions of the Seriousness of Crime - Visschers, Jonas (European journal on criminal policy and research, 2025)
The seriousness of crime is a key concept in criminal policy. Given the scarcity of empirical assessments, public perceptions of crime seriousness are often presented as the evidence base for policy decisions. However, public perceptions of crime seriousness have hardly been measured in recent years and have not been compared to those of criminal justice officials, though the latter are likely to differ. Drawing on a novel conceptualisation of perceived crime seriousness, we measure and compare crime seriousness perceptions of the public and the police, and investigate the logic both groups use in assessing crime seriousness. Yielding data from 2,528 residents and 396 police officers in Flanders, our study indicates that public and police perceptions of crime seriousness are similar, but not identical. It also shows that both groups rely on wrongfulness and harmfulness to assess crime seriousness, but that the relative importance of these dimensions differs.